A Model of the CAS-OB Process for Online Applications. Issue 17 (2015) - Rotevatn, Torstein; Wasbø, Stein O.; Järvinen, Mika; Fabritius, Timo; Ollila, Seppo; Hammervold, Andreas; Blasio, Cataldo De
Abstract: An existing model of the CAS-OB process has been optimized for online use by carefully selecting state variables, removal of implicit algebraic equations, and reformulating the system as a set of ordinary differential equations. The revised model has been validated with the previous model as well as with process measurements. Further, the model has been implemented in the Cybernetica™ CENIT framework for online applications. Recursive parameter estimation by Kalman-filtering and model predictive control have been demonstrated.